Potential antibacterial activity of crude extracts and silver nanoparticles synthesized from Sargassum wightii - Thirumalairaj, Vinoth Kumar; Vijayan, Mahitha Puthanpurayal; Durairaj, Geetharamani; Shanmugaasokan, Lakshmanasenthil; Yesudas, Rincy; Gunasekaran, Suja (International Current Pharmaceutical Journal, 2014)
The present work investigates the antibacterial activity of silver nanoparticles (Ag-NPs) synthesized by biological method using Sargassum wightii. The fresh live seaweed was collected from the Mandapam coast of Tamilnadu, India. Solvent extract was prepared using acetone, petroleum ether and methanol. Aqueous extract of the seaweed was also used for the synthesis of silver Ag-NPs. Seaweed extract is used as a reducing agent of 2mM silver nitrate solution for the synthesis of Ag-NPs. Periodical monitoring of reaction mixture was done using UV-vis spectroscopy at 300-750 nm. The scanning electron microscopy (SEM) of the sample confirms the presence of Ag-NPs. The antibacterial activity of solvent extract was done by Minimal inhibitory concentration (MIC) assay. The methanol extract of the seaweed at a concentration of 250µg/ml exhibited potent antimicrobial activity against the test microorganism. The zone of inhibition ranging from 8-14 mm was observed with different extracts. The antibacterial activity of the synthesized Ag-NPs against the organism was also done by MIC test. The MIC of Ag-NPs was found to be 130µg/ml for all pathogenic microorganisms selected for the study. The zone of inhibition against Bacillus cereus, Bacillus anhtracis, Staphylococcus aureus and Vibrio alginoyticus were found to be 10, 8, 10 and 9 mm, respectively. The synthesized Ag-NPs exhibited significant antimicrobial activity against the selected microorganisms than the solvent extract of seaweed. DOI: http://dx.doi.org/10.3329/icpj.v3i10.20337 International Current Pharmaceutical Journal, September 2014, 3(10): 322-325